PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL KOOPERATIF TIPE BERPIKIR BERPASANGAN DI SEKOLAH DASAR LABORATORIUM UM KOTA MALANG - Antonius Alam Wicaksono; Nathasa Pramudita Irianti (Universitas Tribhuwana Tunggadewi, 2022)
This study aims to determine the improvement of students' Indonesian learning outcomes through the application of the cooperative model of the pair-type cooperative model for elementary schools in the Malang City UM laboratory. This research was a Classroom Action Research (CAR) with a sample of all second grade students. The data analysis technique was used through quantitative and qualitative data analysis. The results showed that there was a significant increase in student learning outcomes from each cycle, where the percentage of completeness from 20% to 100%, with details as many as 13 students who scored 80-100 (65%), and 7 other students scored 60-79 (35%). These results indicate that the application of this type of paired cooperative learning model is able to assist students in solving problems related to everyday problems, and is also able to develop students' communicative abilities, increase independent learning and build relationships with each other.